Nationwide Prevalence of Dental Caries in Turkish Children: A Meta-Analysis - Ezgi Eroğlu Çakmakoğlu; Ayşe Günay (Children)
Objectives: This meta-analysis aims to estimate the pooled prevalence of dental caries among children in Turkey by synthesizing national evidence from theses and peer-reviewed articles published between 2000 and 2024. Methods: Studies were retrieved from the YÖK Thesis Database and Google Scholar using keywords such as ‘Caries Prevalence’ and ‘Primary Tooth.’ PubMed was used to cross-check peer-reviewed articles. A total of 28 studies and 29 data points including 40,244 children aged approximately 2 to 15 years were included. PRISMA guidelines were followed. Heterogeneity was assessed using the I2 index, and publication bias was evaluated with an Egger’s test and funnel plots. Results: The pooled prevalence of dental caries among Turkish children was 75.6% (95% CI: 70.8–79.8%). Substantial heterogeneity was observed (I2 = 98.4%), but no significant publication bias was detected. Conclusions: Dental caries remains a significant public health issue among children in Turkey. Targeted preventive measures—such as nationwide dental screenings and school-based fluoride programs—are urgently needed.